The information-motivation-behavioral skills model of ART adherence in a Deep South HIV+ clinic sample. - Amico, K Rivet; Barta, William; Konkle-Parker, Deborah J; Fisher, Jeffrey D; Cornman, Deborah H; Shuper, Paul A; Fisher, William A (AIDS and behavior, 2009)
High levels of adherence to antiretroviral therapy (ART) are critical to the management of HIV, yet many people living with HIV do not achieve these levels. There is a substantial body of literature regarding correlates of adherence to ART, and theory-based multivariate models of ART adherence are emerging. The current study assessed the determinants of adherence behavior postulated by the Information-Motivation-Behavioral Skills model of ART adherence in a sample of 149 HIV-positive patients in Mississippi. Structural equation modeling indicated that ART-related information correlated with personal and social motivation, and the two sub-areas of motivation were not intercorrelated. In this Deep South sample, being better informed, socially supported, and perceiving fewer negative consequences of adherence were independently related to stronger behavioral skills for taking medications, which in turn associated with self-reported adherence. The IMB model of ART adherence appeared to well characterize the complexities of adherence for this sample.
Keywords: Anti-HIV Agents; Female; Health Knowledge, Attitudes, Practice; HIV Infections; Humans; Male; Medication Adherence; Mississippi; Models, Psychological; Motivation; Patient Education as Topic; Psychological Tests